2005
DOI: 10.1080/10446670410001722230
|View full text |Cite
|
Sign up to set email alerts
|

A Novel System to Diagnose Cutaneous Adverse Drug Reactions Employing the Cellscan—Comparison with Histamine Releasing Test and Inf‐γ Releasing Test

Abstract: Background: There are several mechanisms to describe allergic drug reactions yet the methods to diagnose them are limited.Objective: To compare several conventional clinical and laboratory methods to diagnose skin reactions to drugs to a new method of diagnosing drug reactions by the CellScan system.Methods: The study entailed 21 patients who were diagnosed as suffering from drug eruptions, and 105 healthy controls with no history of drug allergy. The drugs were classified into two groups according to suspicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Due to the reemergence of generalized urticaria following the rechallenge with MMF, we concluded that the patient had developed the hypersensitivity reaction to MMF. In addition, the rechallenge with MMF confirmed the results suggested by the in vitro CellScan analysis [13]. …”
Section: Case Reportsupporting
confidence: 69%
See 2 more Smart Citations
“…Due to the reemergence of generalized urticaria following the rechallenge with MMF, we concluded that the patient had developed the hypersensitivity reaction to MMF. In addition, the rechallenge with MMF confirmed the results suggested by the in vitro CellScan analysis [13]. …”
Section: Case Reportsupporting
confidence: 69%
“…Briefly, 20 ml of blood was collected and mononuclear cells were separated in a Ficoll gradient and incubated with the following suspected drugs: ofloxacin, clindamycin, plaquenil, MCR and MMF. Changes in fluorescence polarization were measured using the CellScan method [13]. Results were positive for ofloxacin and MMF, suggesting that these drugs may have been responsible for the urticaria.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…These preliminary findings illustrate the potential role for the CellScan in the detection of drugs responsible for adverse reactions. 30…”
Section: Monitoring Drug Efficacy and Drug-induced Hypersensitivitymentioning
confidence: 99%
“…Since this system was first introduced by Deutsh and Weinreb in 1994 20 it has been widely used to detect activation of lymphocytes both in physiological 21 and pathological situations including cancer, autoimmune disorders and atherosclerosis 22–25 . In 2005, the Cellscan has been introduced as a novel in vitro test to diagnose cutaneous ADR 26,27 . Although its diagnostic potential has been demonstrated with sensitivity of 87% and specificity of 53%, the accuracy of the test has not been tested according to the type of drug, type of rash or clinical probability of patients for having a cutaneous adverse reaction.…”
Section: Introductionmentioning
confidence: 99%